Trypanocidal activity of the proteasome inhibitor and anti-cancer drug bortezomib - Steverding, Dietmar (BioMed Central, 2009)
The proteasome inhibitor and anti-cancer drug bortezomib was tested for in vitro activity against bloodstream forms of Trypanosoma brucei. The concentrations of bortezomib required to reduce the growth rate by 50% and to kill all trypanosomes were 3.3 nM and 10 nM, respectively. In addition, bortezomib was 10 times more toxic to trypanosomes than to human HL-60 cells. Moreover, exposure of trypanosomes to 10 nM bortezomib for 16 h was enough to kill 90% of the parasites following incubation in fresh medium. However, proteasomal peptidase activities of trypanosomes exposed to bortezomib were only inhibited by 10% and 30% indicating that the proteasome is not the main target of the drug. The results suggest that bortezomib may be useful as drug for the treatment of human African trypanosomiasis.